2013
DOI: 10.1590/s1413-81232013000900024
|View full text |Cite
|
Sign up to set email alerts
|

O direito de viver a própria morte e sua constitucionalidade

Abstract: O direito de viver a própria morte e sua constitucionalidadeThe right to live one's own death and its constitutionality

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 0 publications
1
15
0
11
Order By: Relevance
“…The present study found evidence of the intention of prolonging the lives of terminally ill patients from the perspective of nurses, doctors and family caregivers, reflecting limitations in AWD application. From this point of view, this research confirms the argument that the culture of medicalization of life forces us to continue to postpone its final moment (15) . With that in mind, and emphasizing the research findings, doctors seem to be more afraid of investing too little rather than doing too much for patients, and patients seem to feel the same way and are likely to be grateful that additional tests and exams are carried out.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The present study found evidence of the intention of prolonging the lives of terminally ill patients from the perspective of nurses, doctors and family caregivers, reflecting limitations in AWD application. From this point of view, this research confirms the argument that the culture of medicalization of life forces us to continue to postpone its final moment (15) . With that in mind, and emphasizing the research findings, doctors seem to be more afraid of investing too little rather than doing too much for patients, and patients seem to feel the same way and are likely to be grateful that additional tests and exams are carried out.…”
Section: Discussionsupporting
confidence: 83%
“…Besides ethical conflicts that may weaken effects of the Resolution, professionals may face conflicts of opinion that increase their uncertainty about decisionmaking. At such times, physicians who face possible threats and risks of suffering lawsuits may ignore patients' ADW, preferring to follow family guidance (15) . Distribution of patients prior preference can be an important element of this argument (20) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scientific, technical progress of health not only increased the hope of living more and better, but also it generated difficult and complex situations about the end of life. 5,6 Science prioritizes the pursuit of health and healing, understanding death as a failure and defeat. In diseases with slow development and poor prognosis, treatment may be more painful than the disease, and obstinate behaviors that are characterized by the continuation of healing treatments may occur, even when it is no longer possible, leading to a medically slow and prolonged death, accompanied by suffering.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of a definitive positioning in the legislative field can increase the insecurity of professionals to follow the decisions of a patient 14,15 . Research that attempted to identify the attitude of professionals regarding the living showed that only 60.77% of respondents said they followed the decisions of patients 16 …”
mentioning
confidence: 99%